Impacts of Culture Technique and Estuarine Position on Oyster Mariculture-mediated Nitrogen Removal in Temperate Estuaries - Nicholas P. Funnell; Suzanne P. Thompson; Chelsea M. Brown; F. Joel Fodrie; Michael F. Piehler (Estuaries and Coasts, 2026)

The Sedimentary Geochemistry and Paleoenvironments Project Phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

Genetic algorithm optimization of nuclear criticality experiment for reduction of intermediate-energy 239Pu nuclear data uncertainties - Noah Kleedtke; Theresa Cutler; Denise Neudecker; Jesson Hutchinson; Peter Brain; Nicholas Thompson; Robert C. Little (Annals of Nuclear Energy, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

The Sedimentary geochemistry and paleoenvironments project phase 2 data release: An open data resource for the study of Earth's environmental history - Úna C. Farrell; Hunter C. Olson; Maya O. Thompson; Michelle L. Abshire; Oyeleye O. Adeboye; Anne-Sofie C. Ahm; Lewis J. Alcott; Thomas J. Algeo; Ross P. Anderson; Arif H. Ansari; Lucas Pinto Heckert Bastos; Kohen W. Bauer; et al. (Chemical Geology, 2026)

The Toxicology Investigators Consortium 2024 Annual Report - Kim Aldy; Shao Li; Mari Costantini; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; Michael Abesamis; Faiz Ahmed; Salman Ahsan; Peter Akpunonu; Adam Algren; et al. (Journal of Medical Toxicology, 2026)

Deep neural networks and genome-wide associations reveal the polygenic architecture of local brain aging - Nicholas J. Kim; Ayati Mishra; Nahian F. Chowdhury; Samuel D. Anderson; Owen M. Vega; Nikhil N. Chaudhari; Kenneth H. Buetow; Paul M. Thompson; Andrei Irimia (GeroScience, 2025)
Local brain age (LBA) is a regional metric of brain aging that offers a spatially resolved alternative to global brain age, but whose genetic basis is unexplored. This study reports the first genome-wide association study of cortical LBA, as estimated by a deep neural network from the T 1 -weighted magnetic resonance images of 41,708 cognitively normal adults in the UK Biobank. We identified 1,212 single-nucleotide polymorphisms (SNPs) significantly associated with LBA in at least one brain region. Genes mapped to these SNPs are involved in developmental, metabolic, immune, and cytoskeletal pathways. Dimensionality reduction of SNP association profiles uncovered three clusters linked to morphogenetic, cytoskeletal, and immuno-epigenetic processes, helping to relate neuroanatomic, immunosenescent and epigenetic mechanisms of brain aging. Top variants are mapped to KCNK2 , NUAK1 , GMNC , MSL2 , and to other genes implicated in neurodevelopment and neurodegeneration. Spatial clustering of LBA-associated variants in default mode, limbic, and motor network regions parallel regional vulnerability to Alzheimer’s disease and frontotemporal dementia. These findings establish a polygenic architecture for regional brain aging and support LBA as a genetically informed phenotype for studying aging-related neurodegeneration. Our results suggest that cortical aging is not governed by isolated loci but by coordinated genetic programs—rooted in development, metabolism, and cellular structure—that confer lifelong patterns of regional brain vulnerability and resilience. This first genetic dissection of spatially specific brain aging reveals a polygenic landscape of coordinated genetic programs, developmentally encoded and metabolically maintained during senescence. This study reframes aging as an anatomically specific genetic process reflecting the varying structural vulnerabilities observed across neurodegenerative diseases.

Adaptive water body detection: Integrating deep learning, normalised difference water index, and vector data for farm dam water monitoring with OmniWaterMask - Nicholas Wright; John M.A. Duncan; J. Nik Callow; Sally E. Thompson; Richard J. George (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Archival data reveals human impacts on Blanding’s turtle population persistence - Richard King; Chris Anchor; Whitney J.B. Anthonysamy; Sara Denham; Mike Dreslik; Nicholas Dunham; Gary Glowacki; Callie K. Golba; William Graser; Cindi Jablonski; Fredric Janzen; Ethan J. Kessler; et al. (Journal for Nature Conservation, 2025)

Beta-Amino Carboxylate (BAC) non-aqueous physical solvents for enhanced CO2 separations in pre-combustion carbon capture, industrial CO2 capture, and biogas upgrading processes - Jeffrey T. Culp; Robert L. Thompson; Kathryn H. Smith; David Hopkinson; Nicholas Siefert (International Journal of Greenhouse Gas Control, 2025)

A Combination of Mechanical, Chemical, and Thermal Pretreatments of Agricultural Feedstocks Enhances Biomethane Yields in Advanced Anaerobic Digestion - Nichola Austen; Helen Theaker; Nicholas A. Tenci; Alan Beesley; Ian P. Thompson (BioEnergy Research, 2025)
Multi-step advanced anaerobic digestion (AAD) pretreatment of feedstocks increases biogas yields compared to non-pretreated feedstocks, and is key to the processing of recalcitrant lignocellulosic feedstock to make commercial biogas production more economically viable. Here, we present several low energy and eco-friendly pretreatments to commercially relevant lignocellulosic feedstocks (rye and maize), to increase biomethane yields. In this study, the impact of two heating treatments, 55 °C and at 80 °C, the addition of a bio-organic catalyst (BOC), and mechanical particle size reduction by cavitation were investigated. For both feedstocks, thermal pretreatment significantly increased both solubility and enhanced biogas yield (8.6–136.6%), with maize responding better to a temperature of 55 °C (136.6% increase) and rye to 80 °C (62% increase). The BOC addition enhanced the rye yield (14%) but decreased from maize (4%), and cavitation enhanced the biochemical methane potential (BMP) of rye (38.7%) but had an inhibitory effect on maize (10.6%). The results of this multi-process study demonstrate the efficacy of low energy pretreatments for lignocellulosic material that can be applied to existing AD plants.

Training sensor-agnostic deep learning models for remote sensing: Achieving state-of-the-art cloud and cloud shadow identification with OmniCloudMask - Nicholas Wright; John M.A. Duncan; J. Nik Callow; Sally E. Thompson; Richard J. George (Remote Sensing of Environment, 2025)

Registry versus claims-based index dates for studies of cancer diagnosis in administrative data - Sarah E. Soppe; Sharon Peacock Hinton; Jamie C. Halula; Jennifer L. Lund; Chris D. Baggett; Sandi L. Pruitt; Megan A. Mullins; Ellis C. Dillon; Matthew E. Barclay; Matthew Thompson; Nicholas Pettit; Georgios Lyratzopoulos; et al. (Cancer Causes & Control, 2025)

BioTIME 2.0: Expanding and Improving a Database of Biodiversity Time Series - Maria Dornelas; Laura H. Antão; Amanda E. Bates; Viviana Brambilla; Jonathan M. Chase; Cher F. Y. Chow; Ada Fontrodona‐Eslava; Anne E. Magurran; Inês S. Martins; Faye Moyes; Alban Sagouis; Samuel Adu‐Acheampong; et al. (Global Ecology and Biogeography, 2025)
Motivation Here, we make available a second version of the BioTIME database, which compiles records of abundance estimates for species in sample events of ecological assemblages through time. The updated version expands version 1.0 of the database by doubling the number of studies and includes substantial additional curation to the taxonomic accuracy of the records, as well as the metadata. Moreover, we now provide an R package (BioTIMEr) to facilitate use of the database. Main Types of Variables Included The database is composed of one main data table containing the abundance records and 11 metadata tables. The data are organised in a hierarchy of scales where 11,989,233 records are nested in 1,603,067 sample events, from 553,253 sampling locations, which are nested in 708 studies. A study is defined as a sampling methodology applied to an assemblage for a minimum of 2 years. Spatial Location and Grain Sampling locations in BioTIME are distributed across the planet, including marine, terrestrial and freshwater realms. Spatial grain size and extent vary across studies depending on sampling methodology. We recommend gridding of sampling locations into areas of consistent size. Time Period and Grain The earliest time series in BioTIME start in 1874, and the most recent records are from 2023. Temporal grain and duration vary across studies. We recommend doing sample‐level rarefaction to ensure consistent sampling effort through time before calculating any diversity metric. Major Taxa and Level of Measurement The database includes any eukaryotic taxa, with a combined total of 56,400 taxa. Software Format csv and. SQL.

Genetic Insights into Brain Morphology: a Genome-Wide Association Study of Cortical Thickness and T1-Weighted MRI Gray Matter-White Matter Intensity Contrast - Nicholas J. Kim; Nahian F. Chowdhury; Kenneth H. Buetow; Paul M. Thompson; Andrei Irimia (Neuroinformatics, 2025)
In T 1 -weighted magnetic resonance imaging (MRI), cortical thickness (CT) and gray-white matter contrast (GWC) capture brain morphological traits and vary with age-related disease. To gain insight into genetic factors underlying brain structure and dynamics observed during neurodegeneration, this genome-wide association study (GWAS) quantifies the relationship between single nucleotide polymorphisms (SNPs) and both CT and GWC in UK Biobank participants ( N = 43,002). To our knowledge, this is the first GWAS to investigate the genetic determinants of cortical T 1 -MRI GWC in humans. We found 251 SNPs associated with CT or GWC for at least 1% of cortical locations, including 42 for both CT and GWC; 127 for only CT; and 82 for only GWC. Identified SNPs include rs1080066 (THSB1, featuring the strongest association with both CT and GWC), rs13107325 (SLC39A8, linked to CT at the largest number of cortical locations), and rs864736 (KCNK2, associated with GWC at the largest number of cortical locations). Dimensionality reduction reveals three major gene ontologies constraining CT (neural signaling, ion transport, cell migration) and four constraining GWC (neural cell development, cellular homeostasis, tissue repair, ion transport). Our findings provide insight into genetic determinants of GWC and CT, highlighting pathways associated with brain anatomy and dynamics of neurodegeneration. These insights can assist the development of gene therapies and treatments targeting brain diseases.

Global Marine Flyways Identified for Long‐Distance Migrating Seabirds From Tracking Data - Joanne M. Morten; Ana P. B. Carneiro; Martin Beal; Anne‐Sophie Bonnet‐Lebrun; Maria P. Dias; Marie‐Morgane Rouyer; Autumn‐Lynn Harrison; Jacob González‐Solís; Victoria R. Jones; Virginia A. Garcia Alonso; Michelle Antolos; Javier A. Arata; et al. (Global Ecology and Biogeography, 2025)
Aim To identify the broad‐scale oceanic migration routes (‘marine flyways’) used by multiple pelagic, long‐distance migratory seabirds based on a global compilation of tracking data. Location Global. Time Period 1989–2023. Major Taxa Studied Seabirds (Families: Phaethontidae, Hydrobatidae, Diomedeidae, Procellariidae, Laridae and Stercorariidae). Methods We collated a comprehensive global tracking dataset that included the migratory routes of 48 pelagic and long‐distance migrating seabird species across the Atlantic, Indian, Pacific and Southern Oceans. We grouped individuals that followed similar routes, independent of species or timings of migration, using a dynamic time warping clustering approach. We visualised the routes of each cluster using a line density analysis and used knowledge of seabird spatial ecology to combine the clusters to identify the broad‐scale flyways followed by most pelagic migratory seabirds tracked to‐date at an ocean‐basin scale. Results Six marine flyways were identified across the world's oceans: the Atlantic Ocean Flyway, North Indian Ocean Flyway, East Indian Ocean Flyway, West Pacific Ocean Flyway, Pacific Ocean Flyway and Southern Ocean Flyway. Generally, the flyways were used bidirectionally, and individuals either followed sections of a flyway, a complete flyway, or their movements linked two or more flyways. Transhemispheric figure‐of‐eight routes in the Atlantic and Pacific oceans, and a circumnavigation flyway in the Southern Ocean correspond with major wind ‐ driven ocean currents. Main Conclusions The marine flyways identified demonstrate that pelagic seabirds have similar and repeatable migration routes across ocean‐basin scales. Our study highlights the need to account for connectivity in seabird conservation and provides a framework for international cooperation.

Agricultural commercialisation and food consumption: pathways and trade-offs across four African contexts - Amrita Saha; Jody Harris; Nicholas Nisbett; John Thompson (Food Security, 2024)
The relationship between agricultural commercialisation and nutrition is empirically contested, with findings suggesting different trends for different indicators, and across different contexts. Using novel cross-sectional survey data from a study of commercialisation in four African countries, this paper aims to understand associations and trade-offs between agricultural commercialisation and food consumption using three different indicators: household perceptions of their own food security; the dietary diversity of adult women and men; and the consumption of unhealthy ultra-processed foods and drinks. We find that a higher level of commercialisation is associated with respondents perceiving the household as more food secure in three countries and hypothesise that this relationship only holds where food price inflation remains low. Perception of better food security is subsequently associated with better reported dietary diversity, but diversity remains low in all countries even in the most commercialised households, and men’s dietary diversity overtakes women’s, on average, at higher levels of commercialisation. Ultra-processed foods were not highly consumed in our samples but were also linked with increasing commercialisation. Through this analysis, we show that commercialization and food consumption outcomes are linked in both positive and negative ways – and that both, retaining own food production, and the food market context, plays a moderating role, as does household experience of uncertainty in transition to commercial agriculture. Findings for policy in the context of inevitable but highly varied forms of agricultural commercialisation in Africa therefore include ensuring that diverse nutritious foods are available and affordable in local markets, but also that household food security and diets are socially supported through the process of transition where commercialisation is pursued.

Characterizing variability in geochemistry and mineralogy of western US dust sources - Abby L. Mangum; Gregory T. Carling; Barry R. Bickmore; Nicholas Webb; DeTiare L. Leifi; Janice Brahney; Diego P. Fernandez; Kevin A. Rey; Stephen T. Nelson; Landon Burgener; Joshua J. LeMonte; Alyssa N. Thompson; et al. (Aeolian Research, 2024)

Cooling-induced geomechanical response of North Sea reservoirs, and relevance for CO2 storage monitoring - Lars Grande; Luke Griffiths; Joonsang Park; Elin Skurtveit; Nicholas Thompson (International Journal of Greenhouse Gas Control, 2024)

The Toxicology Investigators Consortium 2023 Annual Report - Adrienne Hughes; Alexandra Amaducci; Sharan L. Campleman; Shao Li; Mari Costantini; Meghan B. Spyres; Hannah Spungen; Jessica Kent; Alyssa Falise; Rachel Culbreth; Paul M. Wax; Jeffery Brent; et al. (Journal of Medical Toxicology, 2024)

CloudS2Mask: A novel deep learning approach for improved cloud and cloud shadow masking in Sentinel-2 imagery - Nicholas Wright; John M.A. Duncan; J. Nik Callow; Sally E. Thompson; Richard J. George (Remote Sensing of Environment, 2024)

Red seaweed as an abundant, natural methanogenesis inhibitor for industrial biorefinery - Nicholas A. Tenci; Fariza Ammam; Nichola Austen; Wei E. Huang; Ian P. Thompson (Journal of Cleaner Production, 2024)

Tracking data highlight the importance of human-induced mortality for large migratory birds at a flyway scale - Juan Serratosa; Steffen Oppel; Shay Rotics; Andrea Santangeli; Stuart H.M. Butchart; Luis S. Cano-Alonso; Jose Luis Tellería; Ryno Kemp; Aaron Nicholas; Aigars Kalvāns; Aitor Galarza; Aldina M.A. Franco; et al. (Biological Conservation, 2024)

Systematics and biogeography of Bacopa (Plantaginaceae) - Nicholas P. Tippery; Daniel Gonzalez-Socoloske; Frederik Leliaert; Tai A. Thompson; André Vito Scatigna; Vinicius Castro Souza (Plant Systematics and Evolution, 2024)

Metrics and Considerations for Evaluating How Forest Treatments Alter Wildfire Behavior and Effects - Anthony G Vorster; Camille Stevens-Rumann; Nicholas Young; Brian Woodward; Christopher Tsz Hin Choi; Marin E Chambers; Antony S Cheng; Michael Caggiano; Courtney Schultz; Matthew Thompson; Michelle Greiner; Greg Aplet; et al. (Journal of Forestry, 2024)
The influence of forest treatments on wildfire effects is challenging to interpret. This is, in part, because the impact forest treatments have on wildfire can be slight and variable across many factors. Effectiveness of a treatment also depends on the metric considered. We present and define human–fire interaction, fire behavior, and ecological metrics of forest treatment effects on wildfire and discuss important considerations and recommendations for evaluating treatments. We demonstrate these concepts using a case study from the Cameron Peak Fire in Colorado, USA. Pre-fire forest treatments generally, but not always, experienced reduced burn severity, particularly when surface fuels were reduced. Treatments in the Cameron Peak Fire have also been documented as increasing tree survivorship, aiding suppression efforts, promoting firefighter safety, and influencing fire spread. However, the impacts of pre-fire management on primary landscape-scale objectives, like watershed protection, are unknown. Discussions about the influence of pre-fire treatments on fire effects must define the indicator(s) being assessed, as the same treatment may be considered successful under one measure but not others. Thus, it is critical to bring a common language and understanding to conversations about treatment effects and advance efforts to evaluate the range of treatment effects, thus supporting treatment planning.

A paleoecological investigation of recent cyanobacterial blooms and their drivers in two contrasting lakes - Caitlin Wheeler; John K. Pearman; Jamie D. Howarth; Marcus J. Vandergoes; Katherine Holt; Steven A. Trewick; Xun Li; Lucy Thompson; Georgia Thomson-Laing; Mailys Picard; Chris Moy; Nicholas P. Mckay; et al. (Harmful Algae, 2024)

Integrating Remote Sensing with Ground-based Observations to Quantify the Effects of an Extreme Freeze Event on Black Mangroves (Avicennia germinans) at the Landscape Scale - Melinda Martinez; Michael J. Osland; James B. Grace; Nicholas M. Enwright; Camille L. Stagg; Simen Kaalstad; Gordon H. Anderson; Anna R. Armitage; Just Cebrian; Karen L. Cummins; Richard H. Day; Donna J. Devlin; et al. (Ecosystems, 2024)

Subcritical neutron noise measurements for plutonium systems with varying geometry and mass - Jesson Hutchinson; Alexander R. Clark; Theresa Cutler; Wim Haeck; Noah Kleedtke; Juliann Lamproe; Denise Neudecker; Michael Rising; Nicholas Thompson; Robert Little (Annals of Nuclear Energy, 2024)

TEA of the CO2 capture process in pre-combustion applications using thirty-five physical solvents: Predictions with ANN - Husain E. Ashkanani; Rui Wang; Wei Shi; Nicholas S. Siefert; Robert L. Thompson; Kathryn H. Smith; Janice A. Steckel; Isaac K. Gamwo; David Hopkinson; Kevin Resnik; Badie I. Morsi (International Journal of Greenhouse Gas Control, 2023)

The Toxicology Investigators Consortium 2022 Annual Report - Alexandra M. Amaducci; Sharan L. Campleman; Shao Li; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; Rachel E. Culbreth; Paul M. Wax; Jeffrey Brent; Kim Aldy; Jennifer Acciani; et al. (Journal of Medical Toxicology, 2023)

Enhanced School Nutrition Strategies, Training, Action Plans, and Resources (E-STAR) Grant - Whitney Vance; Monal Shroff; Janet Gaffke; Nicholas Thompson; Kristina Talarek; Jordan Kamal; Viki Lorraine (Journal of Nutrition Education and Behavior, 2023)

Geographic and taxonomic variation in adaptive capacity among mountain-dwelling small mammals: Implications for conservation status and actions - Erik A. Beever; Jennifer L. Wilkening; Peter D. Billman; Lindsey L. Thurman; Kristina A. Ernest; David H. Wright; Alisha M. Gill; April C. Craighead; Nolan A. Helmstetter; Leona K. Svancara; Meghan J. Camp; Sabuj Bhattacharyya; et al. (Biological Conservation, 2023)

Equal use of Indigenous and scientific knowledge in species assessments: A case study from the Northwest Territories, Canada - Claire L. Singer; Mélanie R. Routh; Michele J. Grabke; Leon Andrew; Suzanne Carrière; Aimee Guile; Alestine Andre; Allison Thompson; Deborah Simmons; Kaytlin Cooper; Lynda Yonge; Moise Rabesca; et al. (Biological Conservation, 2023)

Elevated concentrations of organic and inorganic forms of iron in plant-based diets for channel catfish prevent anemia but damage liver and intestine, respectively, without impacting growth performance - Isaac Buyinza; Rebecca Lochmann; Amit K. Sinha; Michele Thompson; Nicholas Romano; Grace Ramena (Fish Physiology and Biochemistry, 2023)

Performance of hydrophobic physical solvents for pre-combustion CO2 capture at a pilot scale coal gasification facility - Kathryn H. Smith; Husain E. Ashkanani; Robert L. Thompson; Jeffrey T. Culp; Lei Hong; Mike Swanson; Joshua Stanislowski; Wei Shi; Badie I. Morsi; Kevin Resnik; David P. Hopkinson; Nicholas S. Siefert (International Journal of Greenhouse Gas Control, 2023)

Anaerobic co-digestion of Euphorbia tirucalli with pig blood for volatile fatty acid production - Nicholas A. Tenci; Fariza Ammam; Wei E. Huang; Ian P. Thompson (Bioresource Technology Reports, 2023)

Mapping lesion, structural disconnection, and functional disconnection to symptoms in semantic aphasia - Nicholas E. Souter; Xiuyi Wang; Hannah Thompson; Katya Krieger-Redwood; Ajay D. Halai; Matthew A. Lambon Ralph; Michel Thiebaut de Schotten; Elizabeth Jefferies (Brain Structure and Function, 2022)
Patients with semantic aphasia have impaired control of semantic retrieval, often accompanied by executive dysfunction following left hemisphere stroke. Many but not all of these patients have damage to the left inferior frontal gyrus, important for semantic and cognitive control. Yet semantic and cognitive control networks are highly distributed, including posterior as well as anterior components. Accordingly, semantic aphasia might not only reflect local damage but also white matter structural and functional disconnection. Here, we characterise the lesions and predicted patterns of structural and functional disconnection in individuals with semantic aphasia and relate these effects to semantic and executive impairment. Impaired semantic cognition was associated with infarction in distributed left-hemisphere regions, including in the left anterior inferior frontal and posterior temporal cortex. Lesions were associated with executive dysfunction within a set of adjacent but distinct left frontoparietal clusters. Performance on executive tasks was also associated with interhemispheric structural disconnection across the corpus callosum. In contrast, poor semantic cognition was associated with small left-lateralized structurally disconnected clusters, including in the left posterior temporal cortex. Little insight was gained from functional disconnection symptom mapping. These results demonstrate that while left-lateralized semantic and executive control regions are often damaged together in stroke aphasia, these deficits are associated with distinct patterns of structural disconnection, consistent with the bilateral nature of executive control and the left-lateralized yet distributed semantic control network.

The Toxicology Investigators Consortium Case Registry—the 2021 Annual Report - Jennifer S. Love; Dana L. Karshenas; Meghan B. Spyres; Lynn A. Farrugia; A. Min Kang; HoanVu Nguyen; Sharan L. Campleman; Shao Li; Paul M. Wax; Jeffery Brent; Kim Aldy; Michael Abesamis; et al. (Journal of Medical Toxicology, 2022)

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

Common, low-frequency, rare, and ultra-rare coding variants contribute to COVID-19 severity - Chiara Fallerini; Nicola Picchiotti; Margherita Baldassarri; Kristina Zguro; Sergio Daga; Francesca Fava; Elisa Benetti; Sara Amitrano; Mirella Bruttini; Maria Palmieri; Susanna Croci; Mirjam Lista; et al. (Human Genetics, 2022)
The combined impact of common and rare exonic variants in COVID-19 host genetics is currently insufficiently understood. Here, common and rare variants from whole-exome sequencing data of about 4000 SARS-CoV-2-positive individuals were used to define an interpretable machine-learning model for predicting COVID-19 severity. First, variants were converted into separate sets of Boolean features, depending on the absence or the presence of variants in each gene. An ensemble of LASSO logistic regression models was used to identify the most informative Boolean features with respect to the genetic bases of severity. The Boolean features selected by these logistic models were combined into an Integrated PolyGenic Score that offers a synthetic and interpretable index for describing the contribution of host genetics in COVID-19 severity, as demonstrated through testing in several independent cohorts. Selected features belong to ultra-rare, rare, low-frequency, and common variants, including those in linkage disequilibrium with known GWAS loci. Noteworthily, around one quarter of the selected genes are sex-specific. Pathway analysis of the selected genes associated with COVID-19 severity reflected the multi-organ nature of the disease. The proposed model might provide useful information for developing diagnostics and therapeutics, while also being able to guide bedside disease management.

Genetic analyses of gynecological disease identify genetic relationships between uterine fibroids and endometrial cancer, and a novel endometrial cancer genetic risk region at the WNT4 1p36.12 locus - Pik Fang Kho; Sally Mortlock; Frederic Amant; Daniela Annibali; Katie Ashton; John Attia; Paul L. Auer; Matthias W. Beckmann; Amanda Black; Louise Brinton; Daniel D. Buchanan; Stephen J. Chanock; et al. (Human Genetics, 2021)

Pancreatic cancer pathology viewed in the light of evolution - Michaël Noë; Seung-Mo Hong; Laura D. Wood; Elizabeth D. Thompson; Nicholas J. Roberts; Michael G. Goggins; Alison P. Klein; James R. Eshleman; Scott E. Kern; Ralph H. Hruban (Cancer and Metastasis Reviews, 2021)
One way to understand ductal adenocarcinoma of the pancreas (pancreatic cancer) is to view it as unimaginably large numbers of evolving living organisms interacting with their environment. This “evolutionary view” creates both expected and surprising perspectives in all stages of neoplastic progression. Advances in the field will require greater attention to this critical evolutionary prospective.

Quantification and Trends of Rotavirus and Enterovirus in Untreated Sewage Using Reverse Transcription Droplet Digital PCR - Nicholas M. Kiulia; Raul Gonzalez; Hannah Thompson; Tiong Gim Aw; Joan B. Rose (Food and Environmental Virology, 2021)

Corrigendum: OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2021)

Challenges and opportunities for neuroimaging in young patients with traumatic brain injury: a coordinated effort towards advancing discovery from the ENIGMA pediatric moderate/severe TBI group - Emily L Dennis; Karen Caeyenberghs; Robert F Asarnow; Talin Babikian; Brenda Bartnik-Olson; Erin D Bigler; Anthony Figaji; Christopher C Giza; Naomi J Goodrich-Hunsaker; Cooper B Hodges; Kristen R Hoskinson; Marsh Königs; et al. (Brain Imaging and Behavior, 2021)

Differential responses of heather and red grouse to long-term spatio-temporal variation in sheep grazing - Sonja C. Ludwig; Nicholas J. Aebischer; Michael Richardson; Staffan Roos; Des B. A. Thompson; Jeremy D. Wilson; David Baines (Biodiversity and Conservation, 2020)

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

OceanGliders: A Component of the Integrated GOOS - Pierre Testor; Brad de Young; Daniel L. Rudnick; Scott Glenn; Daniel Hayes; Craig M. Lee; Charitha Pattiaratchi; Katherine Hill; Emma Heslop; Victor Turpin; Pekka Alenius; Carlos Barrera; et al. (Frontiers in Marine Science, 2019)
The OceanGliders program started in 2016 to support active coordination and enhancement of global glider activity. OceanGliders contributes to the international efforts of the Global Ocean Observation System (GOOS) for Climate, Ocean Health, and Operational Services. It brings together marine scientists and engineers operating gliders around the world: (1) to observe the long-term physical, biogeochemical, and biological ocean processes and phenomena that are relevant for societal applications; and, (2) to contribute to the GOOS through real-time and delayed mode data dissemination. The OceanGliders program is distributed across national and regional observing systems and significantly contributes to integrated, multi-scale and multi-platform sampling strategies. OceanGliders shares best practices, requirements, and scientific knowledge needed for glider operations, data collection and analysis. It also monitors global glider activity and supports the dissemination of glider data through regional and global databases, in real-time and delayed modes, facilitating data access to the wider community. OceanGliders currently supports national, regional and global initiatives to maintain and expand the capabilities and application of gliders to meet key global challenges such as improved measurement of ocean boundary currents, water transformation and storm forecast.

Spatial resilience of the Great Barrier Reef under cumulative disturbance impacts - Camille Mellin; Samuel Matthews; Kenneth R.N. Anthony; Stuart C. Brown; M. Julian Caley; Kerryn A. Johns; Kate Osborne; Marjetta Puotinen; Angus Thompson; Nicholas H. Wolff; Damien A. Fordham; M. Aaron MacNeil (Global Change Biology, 2019)
In the face of increasing cumulative effects from human and natural disturbances, sustaining coral reefs will require a deeper understanding of the drivers of coral resilience in space and time. Here we develop a high‐resolution, spatially explicit model of coral dynamics on Australia's Great Barrier Reef (GBR). Our model accounts for biological, ecological and environmental processes, as well as spatial variation in water quality and the cumulative effects of coral diseases, bleaching, outbreaks of crown‐of‐thorns starfish ( Acanthaster cf. solaris ), and tropical cyclones. Our projections reconstruct coral cover trajectories between 1996 and 2017 over a total reef area of 14,780 km 2 , predicting a mean annual coral loss of −0.67%/year mostly due to the impact of cyclones, followed by starfish outbreaks and coral bleaching. Coral growth rate was the highest for outer shelf coral communities characterized by digitate and tabulate Acropora spp. and exposed to low seasonal variations in salinity and sea surface temperature, and the lowest for inner‐shelf communities exposed to reduced water quality. We show that coral resilience (defined as the net effect of resistance and recovery following disturbance) was negatively related to the frequency of river plume conditions, and to reef accessibility to a lesser extent. Surprisingly, reef resilience was substantially lower within no‐take marine protected areas, however this difference was mostly driven by the effect of water quality. Our model provides a new validated, spatially explicit platform for identifying the reefs that face the greatest risk of biodiversity loss, and those that have the highest chances to persist under increasing disturbance regimes.

NEOTROPICAL XENARTHRANS: a data set of occurrence of xenarthran species in the Neotropics - Paloma Marques Santos; Adriana Bocchiglieri; Adriano Garcia Chiarello; Adriano Pereira Paglia; Adryelle Moreira; Agnis Cristiane de Souza; Agustin Manuel Abba; Agustin Paviolo; Ailin Gatica; Akyllan Zoppi Medeiro; Alan Nilo Costa; Alberto Gonzalez Gallina; et al. (Ecology, 2019)
Xenarthrans—anteaters, sloths, and armadillos—have essential functions for ecosystem maintenance, such as insect control and nutrient cycling, playing key roles as ecosystem engineers. Because of habitat loss and fragmentation, hunting pressure, and conflicts with domestic dogs, these species have been threatened locally, regionally, or even across their full distribution ranges. The Neotropics harbor 21 species of armadillos, 10 anteaters, and 6 sloths. Our data set includes the families Chlamyphoridae (13), Dasypodidae (7), Myrmecophagidae (3), Bradypodidae (4), and Megalonychidae (2). We have no occurrence data on Dasypus pilosus (Dasypodidae). Regarding Cyclopedidae, until recently, only one species was recognized, but new genetic studies have revealed that the group is represented by seven species. In this data paper, we compiled a total of 42,528 records of 31 species, represented by occurrence and quantitative data, totaling 24,847 unique georeferenced records. The geographic range is from the southern United States, Mexico, and Caribbean countries at the northern portion of the Neotropics, to the austral distribution in Argentina, Paraguay, Chile, and Uruguay. Regarding anteaters, Myrmecophaga tridactyla has the most records ( n = 5,941), and Cyclopes sp. have the fewest ( n = 240). The armadillo species with the most data is Dasypus novemcinctus ( n = 11,588), and the fewest data are recorded for Calyptophractus retusus ( n = 33). With regard to sloth species, Bradypus variegatus has the most records ( n = 962), and Bradypus pygmaeus has the fewest ( n = 12). Our main objective with Neotropical Xenarthrans is to make occurrence and quantitative data available to facilitate more ecological research, particularly if we integrate the xenarthran data with other data sets of Neotropical Series that will become available very soon (i.e., Neotropical Carnivores, Neotropical Invasive Mammals, and Neotropical Hunters and Dogs). Therefore, studies on trophic cascades, hunting pressure, habitat loss, fragmentation effects, species invasion, and climate change effects will be possible with the Neotropical Xenarthrans data set. Please cite this data paper when using its data in publications. We also request that researchers and teachers inform us of how they are using these data.

Rapid Climate-Driven Circulation Changes Threaten Conservation of Endangered North Atlantic Right Whales - Nicholas Record; Jeffrey Runge; Daniel Pendleton; William Balch; Kimberley Davies; Andrew Pershing; Catherine Johnson; Karen Stamieszkin; Rubao Ji; Zhixuan Feng; Scott Kraus; Robert Kenney; et al. (Oceanography, 2019)

Metabolism and Nutritive Role of Cholesterol in the Growth, Gonadal Development, and Reproduction of Crustaceans - Vikas Kumar; Amit Kumar Sinha; Nicholas Romano; Kristy M. Allen; Benjamin A. Bowman; Kenneth R. Thompson; James H. Tidwell (Reviews in Fisheries Science & Aquaculture, 2018)

Human subcortical brain asymmetries in 15,847 people worldwide reveal effects of age and sex - Tulio Guadalupe; Samuel R. Mathias; Theo G. M. vanErp; Christopher D. Whelan; Marcel P. Zwiers; Yoshinari Abe; Lucija Abramovic; Ingrid Agartz; Ole A. Andreassen; Alejandro Arias-Vásquez; Benjamin S. Aribisala; Nicola J. Armstrong; et al. (Brain Imaging and Behavior, 2017)

Rapid divergence of animal personality and syndrome structure across an arid-aquatic habitat matrix - Nicholas P. Moran; Krystina D. Mossop; Ross M. Thompson; David G. Chapple; Bob B. M. Wong (Oecologia, 2017)

Caffeine increases the velocity of rapid eye movements in unfatigued humans - Charlotte J. W. Connell; Benjamin Thompson; Jason Turuwhenua; Robert F. Hess; Nicholas Gant (Psychopharmacology, 2017)

Anxiety is related to indices of cortical maturation in typically developing children and adolescents - Erik Newman; Wesley K. Thompson; Hauke Bartsch; Donald J. Hagler; Chi-Hua Chen; Timothy T. Brown; Joshua M. Kuperman; Connor McCabe; Yoonho Chung; Ondrej Libiger; Natacha Akshoomoff; Cinnamon S. Bloss; et al. (Brain Structure and Function, 2016)

Sustainability of Rooftop Technologies in Cold Climates: Comparative Life Cycle Assessment of White Roofs, Green Roofs, and Photovoltaic Panels - Eduard Cubi; Nicholas F. Zibin; Sarah J. Thompson; Joule Bergerson (Journal of Industrial Ecology, 2016)
Summary Sustainable building rooftop technologies, such as white roofs, green roofs, and photovoltaic(s) (PV) panels, are becoming increasingly implemented as a result of their associated environmental benefits. Studies of these rooftop technologies are often located in hot climates and do not assess their full environmental consequences. Further, current studies tend to focus on one technology and often do not evaluate the full range of technology options using a systematic framework with common assumptions and boundaries. This article evaluates the environmental performance on a life cycle basis of white roofs, green roofs, and roof‐mounted PV in the cold Canadian climate. Solar PV demonstrates the highest environmental performance in all impact categories considered (see complete list in Results section) and is the preferred option from an environmental perspective. Green roofs result in beneficial environmental impacts, although much less significant than those obtained with PV, and are the only rooftop technology that reduces both heating and cooling energy use. The environmental performance of white roofs in cold climates is strongly affected by the heating penalty (i.e., the increase in heating energy use resulting from the high solar reflectance). Although white roofs have been proven an outstanding option in warmer climates, in cold climates, net negative environmental impacts lead to white roof technology not being recommended for general applications in cold climates. A sensitivity analysis shows that the conclusions in this study provide robust insights across Canada and cold climates in general.

Peripheral neuropathy in HIV patients in sub-Saharan Africa failing first-line therapy and the response to second-line ART in the EARNEST trial - Alejandro Arenas-Pinto; Jennifer Thompson; Godfrey Musoro; Hellen Musana; Abbas Lugemwa; Andrew Kambugu; Aggrey Mweemba; Dickens Atwongyeire; Margaret J. Thomason; A. Sarah Walker; Nicholas I. Paton (Journal of NeuroVirology, 2016)

Candidate locus analysis of the TERT–CLPTM1L cancer risk region on chromosome 5p15 identifies multiple independent variants associated with endometrial cancer risk - Luis G. Carvajal-Carmona; Tracy A. O’Mara; Jodie N. Painter; Felicity A. Lose; Joe Dennis; Kyriaki Michailidou; Jonathan P. Tyrer; Shahana Ahmed; Kaltin Ferguson; Catherine S. Healey; Karen Pooley; Jonathan Beesley; et al. (Human Genetics, 2015)

The ENIGMA Consortium: large-scale collaborative analyses of neuroimaging and genetic data - Paul M. Thompson; Jason L. Stein; Sarah E. Medland; Derrek P. Hibar; Alejandro Arias Vasquez; Miguel E. Renteria; Roberto Toro; Neda Jahanshad; Gunter Schumann; Barbara Franke; Margaret J. Wright; Nicholas G. Martin; et al. (Brain Imaging and Behavior, 2014)

Genetic Association Analysis of ITGB3 Polymorphisms with Age at Onset of Schizophrenia - Ke-Sheng Wang; Xuefeng Liu; Tania Bedard Arana; Nicholas Thompson; Henry Weisman; Cecilia Devargas; ChunXiang Mao; Brenda Bin Su; Cynthia Camarillo; Michael A. Escamilla; Chun Xu (Journal of Molecular Neuroscience, 2013)

Genome-wide association identifies genetic variants associated with lentiform nucleus volume in N = 1345 young and elderly subjects - Derrek P. Hibar; Jason L. Stein; April B. Ryles; Omid Kohannim; Neda Jahanshad; Sarah E. Medland; Narelle K. Hansell; Katie L. McMahon; Greig I. de Zubicaray; Grant W. Montgomery; Nicholas G. Martin; Margaret J. Wright; et al. (Brain Imaging and Behavior, 2013)

Spatial Distribution and Exploitation of Trees Gouged by Common Marmosets (Callithrix jacchus) - Cynthia L. Thompson; Nicholas J. Robl; Leonardo César de Oliveira Melo; Mônica M. Valença-Montenegro; Yumma Bernardo Maranhão Valle; Maria Adélia Borstelmann de Oliveira; Christopher J. Vinyard (International Journal of Primatology, 2013)

Sea lamprey orient toward a source of a synthesized pheromone using odor-conditioned rheotaxis - Nicholas S. Johnson; Azizah Muhammad; Henry Thompson; Jongeun Choi; Weiming Li (Behavioral Ecology and Sociobiology, 2012)

Insight in glioma susceptibility through an analysis of 6p22.3, 12p13.33-12.1, 17q22-23.2 and 18q23 SNP genotypes in familial and non-familial glioma - Yanhong Liu; Beatrice S. Melin; Preetha Rajaraman; Zhaoming Wang; Martha Linet; Sanjay Shete; Christopher I. Amos; Ching C. Lau; Michael E. Scheurer; Spiridon Tsavachidis; Georgina N. Armstrong; Richard S. Houlston; et al. (Human Genetics, 2012)

A global synthesis of plant extinction rates in urban areas - Amy K. Hahs; Mark J. McDonnell; Michael A. McCarthy; Peter A. Vesk; Richard T. Corlett; Briony A. Norton; Steven E. Clemants; Richard P. Duncan; Ken Thompson; Mark W. Schwartz; Nicholas S. G. Williams (Ecology Letters, 2009)
Plant extinctions from urban areas are a growing threat to biodiversity worldwide. To minimize this threat, it is critical to understand what factors are influencing plant extinction rates. We compiled plant extinction rate data for 22 cities around the world. Two‐thirds of the variation in plant extinction rates was explained by a combination of the city’s historical development and the current proportion of native vegetation, with the former explaining the greatest variability. As a single variable, the amount of native vegetation remaining also influenced extinction rates, particularly in cities > 200 years old. Our study demonstrates that the legacies of landscape transformations by agrarian and urban development last for hundreds of years, and modern cities potentially carry a large extinction debt. This finding highlights the importance of preserving native vegetation in urban areas and the need for mitigation to minimize potential plant extinctions in the future.

Linking fish population dynamics to habitat conditions: insights from the application of a process-oriented approach to several Great Lakes species - Daniel Hayes; Michael Jones; Nigel Lester; Cindy Chu; Susan Doka; John Netto; Jason Stockwell; Bradley Thompson; Charles K. Minns; Brian Shuter; Nicholas Collins (Reviews in Fish Biology and Fisheries, 2009)

The effect of angiotensin-converting enzyme genotype on acute mountain sickness and summit success in trekkers attempting the summit of Mt. Kilimanjaro (5,895 m) - Nicholas S. Kalson; Julian Thompson; Andrew J. Davies; Suzy Stokes; Mark D. Earl; Adam Whitehead; Ian Tyrrell-Marsh; Hannah Frost; Hugh Montgomery (European Journal of Applied Physiology, 2009)

Meeting the Challenges of Neuroimaging Genetics - Greig I. de Zubicaray; Ming-Chang Chiang; Katie L. McMahon; David W. Shattuck; Arthur W. Toga; Nicholas G. Martin; Margaret J. Wright; Paul M. Thompson (Brain Imaging and Behavior, 2008)

Cross-Scale Responses of Biodiversity to Hurricane and Anthropogenic Disturbance in a Tropical Forest - Michael R. Willig; Christopher P. Bloch; Nicholas Brokaw; Christopher Higgins; Jill Thompson; Craig R. Zimmermann (Ecosystems, 2007)

Initial Adjustments Within a New River Channel: Interactions Between Fluvial Processes, Colonizing Vegetation, and Bank Profile Development - Angela M. Gurnell; Ian P. Morrissey; Angela J. Boitsidis; Tony Bark; Nicholas J. Clifford; Geoffrey E. Petts; Kenneth Thompson (Environmental Management, 2006)